Energy pathway contributions during 60-second upper-body Wingate test in Greco-Roman wrestlers: intermittent versus single forms - Ulupinar, S.; Özbay, S. (Research in Sports Medicine, 2021)
This study aimed to investigate the energy pathway contributions and physiological and performance responses between a 10×6-second intermittent sprint test (IST) and a 60-second single maximal test (SMT). Seventeen highly trained male Greco-Roman wrestlers participated in this study. Participants completed the 60-second upper-body Wingate tests, both intermittent and single forms. The contributions of the oxidative, glycolytic, and ATP-PCr pathways were estimated using mathematical methods based on lactate values and oxygen consumption kinetics of rest, exercise, and recovery phases. The main findings indicated that total energy expenditure (TEE) and the contribution of oxidative, glycolytic, and ATP-PCr pathways were 514kJ, 45%, 11%, and 44% for IST (overall: sprints + rest intervals); 333kJ, 14%, 17%, and 69% for IST (sprints only); and 159kJ, 31%, 38%, and 31% for SMT, respectively. TEE and ATP-PCR pathway contributions were higher in the IST (both overall and sprint only), whereas glycolytic pathway contribution and delta lactate were higher in the SMT. Absolute oxidative contribution was similar, but relative oxidative contribution was higher in the SMT. Additionally, mean power was higher in the IST than SMT, whereas peak power, peak and mean heart rate, and ratings of perceived exertion were similar.